2008
DOI: 10.1007/s10562-008-9636-9
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of n-Octene over Nanoscale HZSM-5 Zeolite

Abstract: Transformation of n-octene has been investigated over nanoscale HZSM-5 at different reaction temperature and contact time. The results show that the main reaction was isomerization of n-octene over 200°C. Hydrogen transfer reaction also occurred at 200°C, but the products were alkanes and cycloolefins instead of aromatics. The aromatization was promoted by high temperature. The maximum selectivity of i-paraffins occurred between 300 and 350°C. Propene, butene and pentene were the primary cracking products. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
0
8
1
Order By: Relevance
“…) were formed in a lower abundance. Furthermore, the C 8 –C 10 aromatics range turned out to be the most abundant range in contrast to that reported in previous studies where C 6 –C 8 BTEX were the most abundant products resulting from the zeolite‐facilitated reforming reactions (Bhan and Delgass, ; Fegade et al, ; Hodala et al, ; Long et al, , ; Nash et al, ; Olson et al, ; Smiešková et al, ), although a relatively large C 9 aromatic fraction was observed in the case of n ‐octene conversion (Long et al, ), corroborating the results obtained in our study.…”
Section: Resultscontrasting
confidence: 87%
See 3 more Smart Citations
“…) were formed in a lower abundance. Furthermore, the C 8 –C 10 aromatics range turned out to be the most abundant range in contrast to that reported in previous studies where C 6 –C 8 BTEX were the most abundant products resulting from the zeolite‐facilitated reforming reactions (Bhan and Delgass, ; Fegade et al, ; Hodala et al, ; Long et al, , ; Nash et al, ; Olson et al, ; Smiešková et al, ), although a relatively large C 9 aromatic fraction was observed in the case of n ‐octene conversion (Long et al, ), corroborating the results obtained in our study.…”
Section: Resultscontrasting
confidence: 87%
“…It was also noted that large amounts of higher‐MW alkylnaphthalene and indane diaromatics were produced, with C 15 naphthalene (i.e., C 5 substituted) being the most abundant. These products were not observed previously in smaller‐size alkene reforming (Bhat and Halgeri, ; Hodala et al, ; Long et al, , ; Maslyanskii et al, ; Nash et al, ; Olson et al, ). Also, acyclic dienes were identified only in Experiments 9 and 10 by their library match, based on the fragmentation pattern, which was different from those of the corresponding isomers, cycloalkenes and acyclic alkynes (the computer‐generated library match was confirmed by the manual case‐to‐case matching of the available MS spectra).…”
Section: Resultsmentioning
confidence: 43%
See 2 more Smart Citations
“…Initially, creating such a varied cavity size design required the use of removable organic templates, but the seminal work of [10] provided a simple template-free nano-size zeolite synthesis protocol. This advancement led to a number of successful applications demonstrating the advantages of using nano-size zeolite catalysts, including but not limited to aromatics' production and ranging from alkene isomerization to triglyceride transesterification [7,[11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%